UPAYA MENINGKATKAN KETERAMPILAN MENCERITAKAN HASIL PENGAMATAN MELALUI METODE PEMBERIAN REWARD AND PUNISHMENT PADA SISWA KELAS V SD NEGERI PLAKARAN BANTUL - Rahmat Kuncahyo; Cicilia Indah Nartani (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
Classroom action research (PTK) aims to describe improvement skill of recounting observation result through giving reward and punishment method at fifth grade students of SD Negeri Plakaran, Bantul. PTK is using a model and MC Taggart Kemmis cycle model. Each cycle consists of four stages: planning, implementation, observation and reflection analysis. The experiment was conducted in the first semester with the subject of the study consists of 24 students. Data collection method in this research use tests, observation and documentation. Descriptive data analysis techniques are used to analyze quantitative and qualitative descriptive test results are used to analyze the results of observation. Results of research conducted shows that the average value of the results of a test of skill telling observations could increase after the action. In pratindakan, the average value obtained 64.16 students with enough category increased to 72.39 with enough categories in cycle I. In the second cycle increased to 81.64 with both categories. The percentage of minimum completeness criteria (KKM) obtained the students also increased, in preaction percentage reached 25%, in the first cycle increased by 54.17% and in the second cycle increased by 83.33%. It shows that the giving reward and punishment method have a positive effect, can improve the recounting skill observation result through giving reward and punishment method at fifth grade students of SD Negeri Plakaran, Bantul academic year 2015/2016.